Venous thromboembolism rates in patients with lower limb immobilization after Achilles tendon injury are unchanged after the introduction of prophylactic aspirin: audit. (26th January 2016) - Braithwaite, I.; Dunbar, L.; Eathorne, A.; Weatherall, M.; Beasley, R.
Abstract : Essentials We audited venous thromboembolism (VTE) in Achilles injuries after the use of prophylactic aspirin. We audited 218 patients with Achilles injury requiring lower limb immobilization for ≥ 1 week. Fourteen patients (6.4%, 95% CI 3.6% to 10.5%) developed symptomatic and confirmed VTE. The incidence was similar to the 6.3% identified in the same patient group prior to the use of aspirin. Summary: Background/Objective: We report a follow‐up audit of the incidence of venous thromboembolism (VTE) in patients requiring lower limb immobilization because of Achilles tendon injury, since the introduction of a policy to routinely prescribe 100 mg of aspirin daily. Patients/Methods: We studied 218 patients aged 18–65 years who attended the Orthopaedic Assessment Unit at Wellington Hospital between January 2013 and December 2014 with Achilles tendon injury requiring lower limb immobilization for ≥ 1 week. Information on assessment of VTE risk, prescription of aspirin and symptomatic VTE occurring within 70 days of immobilization was obtained and compared with the same information collected with the same method in the same patient group between January 2006 and December 2007, before the policy to routinely prescribe aspirin was introduced. Results: A total of 189 of 218 (93%) patients were prescribed aspirin, as compared with 0.5% previously. Fourteen patients (6.4%, 95% confidence interval 3.6–10.5%) developed symptomatic radiologically confirmed VTE (10 distal deep vein thromboses [DVTs], two proximal DVTs, one pulmonary embolism [PE], and one PE with distal DVT). Aspirin was prescribed to all patients who subsequently developed a VTE; in one of 14, a recognized risk factor was documented. The VTE incidence was similar to the 6.3% identified in the previous audit. Conclusion: Lower limb immobilization following Achilles tendon injury confers a high risk of VTE even with aspirin prophylaxis. Consideration should be given to prophylaxis with low molecular weight heparin during lower limb immobilization following Achilles tendon injury, as this has proven efficacy in this clinical situation.